ENHANCING CORPORATE SOCIAL RESPONSIBILITY ACCOUNTABILITY AND TRANSPARENCY THROUGH THE ISLAMIC BASED DIGITAL PLATFORM CSR POINT - Asyraf, Muhammad Fadil; Nurrohman, Maulana Ilyas; Ulya, Hudhwatul; Ningsih, Nabila Aulia (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Corporate Social Responsibility (CSR) is a strategic instrument for enhancing a company's image and competitiveness, while simultaneously fulfilling its legal obligations as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies. However, the implementation of CSR in Indonesia still faces various obstacles, including a lack of transparency, equitable distribution, and accountability. These problems are reflected in cases of misuse of CSR funds, weak oversight, and the large number of companies that have not optimally reported their CSR obligations. To address these challenges, this study proposes CSR Point, a digital platform based on Islamic values designed to improve the accountability and transparency of CSR programs. This platform provides real-time data upload features, a digital tracking system, and a mechanism for submitting proposals by the public to ensure a more equitable and documented program distribution. By integrating with the Sustainable Development Goals (SDGs) and engaging with communities, CSR Point has the potential to transform CSR from a philanthropic activity into an innovative, efficient, and collaborative sustainable development strategy.